2016
DOI: 10.1093/mnras/stw3060
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at the ‘characteristic’ width of molecular cloud filaments

Abstract: Filaments in Herschel molecular cloud images are found to exhibit a "characteristic width". This finding is in tension with spatial power spectra of the data, which show no indication of this characteristic scale. We demonstrate that this discrepancy is a result of the methodology adopted for measuring filament widths. First, we perform the previously used analysis technique on artificial scale-free data, and obtain a peaked width distribution of filament-like structures. Next, we repeat the analysis on three … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 52 publications
12
92
1
Order By: Relevance
“…However, it should be noted that distribution of mean filaments width may be broader than determined in observations (Panopoulou et al 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…However, it should be noted that distribution of mean filaments width may be broader than determined in observations (Panopoulou et al 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…Other authors like Juvela et al (2012) and Hennemann et al (2012) have however reported larger widths of about 0.3 pc, while Panopoulou et al (2016) reported a lesser width of 0.06 ± 0.04 pc. Ysard et al (2013) reported widths varying by a factor of 4, while Panopoulou et al (2017) concluded that a single characteristic width of filaments is inconsistent with observations, and that the narrow distribution is an averaging effect.…”
Section: Filament Widths In Comparison With Herschel Dust Mapsmentioning
confidence: 95%
“…Characterising filaments is fraught with difficulty, and caution must be observed whilst deriving global properties from their mean profiles (e.g. Panopoulou et al 2017). …”
Section: Appendix A: Channel Mapmentioning
confidence: 99%